In vitro propagation and growth of ex vitro Chrysanthemum indicum L. in Da Lat - Lam Dong - Huyen, Phan Xuan; Vy, Truong Ngoc Thao; Hoang, Nguyen Thi Phuong; Hang, Nguyen Thi Thanh; Khiem, Dinh Van (Vietnam Journal of Biotechnology, 2021)
Chrysanthemum indicum plant is a valuable and beneficial herb for human health. In this paper, we present the results of in vitro propagation of this plant in Da Lat. The results showed that MS medium supplemented with 25 g/l sucrose, 9 g/l agar, pH 5.8 was the best for shoot regeneration and growth (shoot height was 2.41 - 2.47 cm, 1 shoot/explant). MS media supplemented with BA (0.1, 0.5, 1, 1.5, 2 mg/l), Kinetin (0.1, 0.5, 1, 1.5, 2 mg/l ) and TDZ (0.1, 0.5, 1 mg/l) were unsuitable for shoot regeneration and growth of C. indicum. The regeneration and growth of shoots on the medium supplemented with 1 g/l of activated charcoal was better than (plant height of 3.45 cm) medium without activated charcoal (plant height of 2.46 cm). MS medium supplemented with 0, 0.1, 0.5, 1 mg/l IBA, 25 g/l sucrose, 9 g/l agar, pH 5,8 were suitable for in vitro root regeneration, rate of root formation was 100%. Coconut fiber powder was the best substrate to transfer the plantlets to the greenhouse, with survial rate of 100%, plantlets grew well. Nitrophoska irrigation was the best for the growth and development of C. indicum cultivated on coconut fiber powder under greenhouse conditions (plant height of 61.70 cm, 100.80 flowers/tree, flower diameter of 1.68 cm, fresh weight of 0.376 g/flower). The results also show that seedlings derived from tissue culture can be used to cultivate C. indicum and C. indicum grew well in the climate of Da Lat - Lam Dong and flowered all year round.